MAYBE Initial complexity problem: 1: T: (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] (1, 1) f3(a, b) -> f2(a, b) (?, 1) f2(a, b) -> f300(a, c) [ a = 0 ] start location: f3 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] (1, 1) f3(a, b) -> f2(a, b) start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a, b) with all transitions in problem 2, the following new transitions are obtained: f3(a, b) -> f2(c + 2, b) [ a >= 1 ] f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] We thus obtain the following problem: 3: T: (1, 2) f3(a, b) -> f2(c + 2, b) [ a >= 1 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c + 2, b) [ a >= 1 ] with all transitions in problem 3, the following new transitions are obtained: f3(a, b) -> f2(c' + 2, b) [ a >= 1 /\ c + 2 >= 1 ] f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] We thus obtain the following problem: 4: T: (1, 3) f3(a, b) -> f2(c' + 2, b) [ a >= 1 /\ c + 2 >= 1 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c' + 2, b) [ a >= 1 /\ c + 2 >= 1 ] with all transitions in problem 4, the following new transitions are obtained: f3(a, b) -> f2(c'' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 ] f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] We thus obtain the following problem: 5: T: (1, 4) f3(a, b) -> f2(c'' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c'' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 ] with all transitions in problem 5, the following new transitions are obtained: f3(a, b) -> f2(c''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 ] f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] We thus obtain the following problem: 6: T: (1, 5) f3(a, b) -> f2(c''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 ] with all transitions in problem 6, the following new transitions are obtained: f3(a, b) -> f2(c'''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 ] f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] We thus obtain the following problem: 7: T: (1, 6) f3(a, b) -> f2(c'''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c'''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 ] with all transitions in problem 7, the following new transitions are obtained: f3(a, b) -> f2(c''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 ] f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] We thus obtain the following problem: 8: T: (1, 7) f3(a, b) -> f2(c''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 ] with all transitions in problem 8, the following new transitions are obtained: f3(a, b) -> f2(c'''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 ] f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] We thus obtain the following problem: 9: T: (1, 8) f3(a, b) -> f2(c'''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c'''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 ] with all transitions in problem 9, the following new transitions are obtained: f3(a, b) -> f2(c''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 ] f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] We thus obtain the following problem: 10: T: (1, 9) f3(a, b) -> f2(c''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 ] (1, 9) f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 ] with all transitions in problem 10, the following new transitions are obtained: f3(a, b) -> f2(c'''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 ] f3(a, b) -> f2(c'''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ 0 >= c''''''' + 3 ] We thus obtain the following problem: 11: T: (1, 10) f3(a, b) -> f2(c'''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 ] (1, 10) f3(a, b) -> f2(c'''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ 0 >= c''''''' + 3 ] (1, 9) f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c'''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 ] with all transitions in problem 11, the following new transitions are obtained: f3(a, b) -> f2(c''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 ] f3(a, b) -> f2(c''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ 0 >= c'''''''' + 3 ] We thus obtain the following problem: 12: T: (1, 11) f3(a, b) -> f2(c''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 ] (1, 11) f3(a, b) -> f2(c''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ 0 >= c'''''''' + 3 ] (1, 10) f3(a, b) -> f2(c'''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ 0 >= c''''''' + 3 ] (1, 9) f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 ] with all transitions in problem 12, the following new transitions are obtained: f3(a, b) -> f2(c'''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 ] f3(a, b) -> f2(c'''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ 0 >= c''''''''' + 3 ] We thus obtain the following problem: 13: T: (1, 12) f3(a, b) -> f2(c'''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 ] (1, 12) f3(a, b) -> f2(c'''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ 0 >= c''''''''' + 3 ] (1, 11) f3(a, b) -> f2(c''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ 0 >= c'''''''' + 3 ] (1, 10) f3(a, b) -> f2(c'''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ 0 >= c''''''' + 3 ] (1, 9) f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c'''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 ] with all transitions in problem 13, the following new transitions are obtained: f3(a, b) -> f2(c''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 ] f3(a, b) -> f2(c''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ 0 >= c'''''''''' + 3 ] We thus obtain the following problem: 14: T: (1, 13) f3(a, b) -> f2(c''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 ] (1, 13) f3(a, b) -> f2(c''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ 0 >= c'''''''''' + 3 ] (1, 12) f3(a, b) -> f2(c'''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ 0 >= c''''''''' + 3 ] (1, 11) f3(a, b) -> f2(c''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ 0 >= c'''''''' + 3 ] (1, 10) f3(a, b) -> f2(c'''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ 0 >= c''''''' + 3 ] (1, 9) f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 ] with all transitions in problem 14, the following new transitions are obtained: f3(a, b) -> f2(c'''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 ] f3(a, b) -> f2(c'''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ 0 >= c''''''''''' + 3 ] We thus obtain the following problem: 15: T: (1, 14) f3(a, b) -> f2(c'''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 ] (1, 14) f3(a, b) -> f2(c'''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ 0 >= c''''''''''' + 3 ] (1, 13) f3(a, b) -> f2(c''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ 0 >= c'''''''''' + 3 ] (1, 12) f3(a, b) -> f2(c'''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ 0 >= c''''''''' + 3 ] (1, 11) f3(a, b) -> f2(c''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ 0 >= c'''''''' + 3 ] (1, 10) f3(a, b) -> f2(c'''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ 0 >= c''''''' + 3 ] (1, 9) f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c'''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 ] with all transitions in problem 15, the following new transitions are obtained: f3(a, b) -> f2(c''''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ c'''''''''''' + 2 >= 1 ] f3(a, b) -> f2(c''''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ 0 >= c'''''''''''' + 3 ] We thus obtain the following problem: 16: T: (1, 15) f3(a, b) -> f2(c''''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ c'''''''''''' + 2 >= 1 ] (1, 15) f3(a, b) -> f2(c''''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ 0 >= c'''''''''''' + 3 ] (1, 14) f3(a, b) -> f2(c'''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ 0 >= c''''''''''' + 3 ] (1, 13) f3(a, b) -> f2(c''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ 0 >= c'''''''''' + 3 ] (1, 12) f3(a, b) -> f2(c'''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ 0 >= c''''''''' + 3 ] (1, 11) f3(a, b) -> f2(c''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ 0 >= c'''''''' + 3 ] (1, 10) f3(a, b) -> f2(c'''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ 0 >= c''''''' + 3 ] (1, 9) f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(c''''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ c'''''''''''' + 2 >= 1 ] with all transitions in problem 16, the following new transitions are obtained: f3(a, b) -> f2(c'''''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ c'''''''''''' + 2 >= 1 /\ c''''''''''''' + 2 >= 1 ] f3(a, b) -> f2(c'''''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ c'''''''''''' + 2 >= 1 /\ 0 >= c''''''''''''' + 3 ] We thus obtain the following problem: 17: T: (1, 16) f3(a, b) -> f2(c'''''''''''''' + 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ c'''''''''''' + 2 >= 1 /\ c''''''''''''' + 2 >= 1 ] (1, 16) f3(a, b) -> f2(c'''''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ c'''''''''''' + 2 >= 1 /\ 0 >= c''''''''''''' + 3 ] (1, 15) f3(a, b) -> f2(c''''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ c''''''''''' + 2 >= 1 /\ 0 >= c'''''''''''' + 3 ] (1, 14) f3(a, b) -> f2(c'''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ c'''''''''' + 2 >= 1 /\ 0 >= c''''''''''' + 3 ] (1, 13) f3(a, b) -> f2(c''''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ c''''''''' + 2 >= 1 /\ 0 >= c'''''''''' + 3 ] (1, 12) f3(a, b) -> f2(c'''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ c'''''''' + 2 >= 1 /\ 0 >= c''''''''' + 3 ] (1, 11) f3(a, b) -> f2(c''''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ c''''''' + 2 >= 1 /\ 0 >= c'''''''' + 3 ] (1, 10) f3(a, b) -> f2(c'''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ c'''''' + 2 >= 1 /\ 0 >= c''''''' + 3 ] (1, 9) f3(a, b) -> f2(c''''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ c''''' + 2 >= 1 /\ 0 >= c'''''' + 3 ] (1, 8) f3(a, b) -> f2(c'''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ c'''' + 2 >= 1 /\ 0 >= c''''' + 3 ] (1, 7) f3(a, b) -> f2(c''''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ c''' + 2 >= 1 /\ 0 >= c'''' + 3 ] (1, 6) f3(a, b) -> f2(c'''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ c'' + 2 >= 1 /\ 0 >= c''' + 3 ] (1, 5) f3(a, b) -> f2(c''' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ c' + 2 >= 1 /\ 0 >= c'' + 3 ] (1, 4) f3(a, b) -> f2(c'' - 2, b) [ a >= 1 /\ c + 2 >= 1 /\ 0 >= c' + 3 ] (1, 3) f3(a, b) -> f2(c' - 2, b) [ a >= 1 /\ 0 >= c + 3 ] (1, 2) f3(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c - 2, b) [ 0 >= a + 1 ] (?, 1) f2(a, b) -> f2(c + 2, b) [ a >= 1 ] start location: f3 leaf cost: 1 Complexity upper bound ? Time: 1.124 sec (SMT: 1.002 sec)